Biological treatment of petrochemical effluent containing benzene, toluene and xylene (BTX) using pseudomonas putida ATCC49128 - Ahmad Bazli, Bustary (2018)
Benzene, toluene, and xylene (BTX) are some examples of aromatic hydrocarbons that are found in petrochemical wastewater. Liquid and gaseous forms of the same are frequently present in municipal treatment plants. In this research, Pseudomonas putida ATCC 49128 was selected for use in the experiments owing to its ability to safely remove the aforementioned aromatic compounds without giving rise to the formation of other hazardous chemicals during the treatment of wastewater. The said experiments were aimed to study P. putida in terms of (1) its growth patterns under normal conditions and in concentrations of BTX, (2) its ability to remove different concentrations of BTX in a shake flask, as well as (3) its ability to remove BTX from actual petrochemical wastewater and simulated solutions. Repeated measurements of BTX concentrations at a petrochemical industrial wastewater effluent tank in Peninsular Malaysia revealed that the maximum values for benzene, toluene, and xylene were 55.2 ppm, 26.9 ppm, and 32.8 ppm respectively. Subsequently, the results of the treatment study showed that the optimal conditions for the growth of P. putida were an orbital shaker speed of 180 rpm, temperature of 37°C, pH 7, and P. putida-nutrient ratio of 1:9. Next, P. putida was made to remove different concentrations of simulated BTX for 48 hours; this procedure was repeated for actual petrochemical wastewater of pH 6, 7, and 8 respectively. This process was analysed using gas chromatography (GC-FID). Evidently, the bacteria were able to reduce the concentrations of BTX in actual petrochemical wastewater (of pH 7) by 85%, 77%, and 70% respectively; for the simulated BTX solution, the values were 87%, 80%, and 72% respectively. In the single simulated BTX solution, the reduction in the concentration of toluene (97%) exceeded those of benzene (93%) and xylene (62%). To conclude, the usage of P. putida ATCC49128 is an effective biological method to reduce the concentrations of BTX in petrochemical wastewater.